Implementación de la Norma ISO 50001 para ahorros sostenibles energéticos y económicos en el sector industrial - Valencia, Guillermo; Rodriguez, Katherin Nahomy; Torregroza Matos, Gloria Raquel; Acevedo, Carlos; Duarte Forero, Jorge (Scientia et Technica, 2020)
Given the growth in energy demand, the limited energy resources, and the high environmental impact of energy generation from fossil fuels, it is vital to find methods to obtain save energy costs in different sectors, such as residential, industrial, transportation sector, and domestic. This paper presents a methodology that allows the implementation of an energy management system following the guidelines of the ISO 50001 standard. A gap analysis was performed to determine the position of the organization with respect to the requirements of the standard, and the next step was the inspection of the plant to find opportunities for improvement that would lead to energy optimization. From the results, six equipment was the cause of the 82% of the energy consumption in the production process, and some recommendation was proposed with the aim to optimize energy consumption. A methodology is proposed for the standard implementation, which can be implemented by different organizations from different fields to achieve savings in energy costs in the plant. Some relevant actions to improve the energy performance of the plant were proposed, such as the optimization of the compressed air system, the reduction of potential numbers of leakage, and the reduction of the working pressure of the system.